Efeito do HPV de alto risco em diferentes faixas etárias com Carcinoma de Células Escamosas de Cabeça e Pescoço - Luciano Marques da Silva (2011)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer and causes 350,000 deaths worldwide each year. This disease comprises epithelial malignancies arising in the paranasal sinuses, nasal cavity, oral cavity, pharynx and larynx, and usually affects men between the sixth and ninth decades of life after long-term exposure to tobacco and alcohol consumption. It has been reported that the incidence of HNSCC among patients under the age of 45 years is increasing worldwide. The factors associated with HNSCC in young are not well established. In this field, high-risk HPV has emerged as a possible agent associated with HNSCC in young patients. The purpose of the current study was to investigate if there is any change in prognosis or in the distribution of HPV-16/18 in young patients compared with adults patients. A longitudinal prospective study was used adjusted for age, gender, TNM staging, smoking and alcohol consumption. HPV was detected by PCR with consensus primers. There is no difference in the frequency of HPV-16/18 positivity when young patients were compared to the adult ones. No association was found among high-risk HPV positivity, gender, smoking habits and anatomical site. High-risk HPV were associated with advanced TNM in bivariate analyses however, it did not impact the survival. Only TNM staging was associated with risk of death. In conclusion, our study supports that age does not alter the frequency of HPV-16/18 in tumors from patients with HNSCC. In addition, HPV-16/18 presence does affect the prognosis of young patients or adults with HNSCC.